Fenomena Nebula dalam Penafsiran Qs. Ar-Rahman Ayat 37: Analisis Komparatif antara Tafsir Klasik dan Tafsir Ilmi Kontemporer - Luthfiyah Az Zahra; Junaidi Junaidi (CV. ALIM'SPUBLISHING, 2026)
Qur’an Surah Ar-Rahman verse 37 is one of the kauniyah (cosmic) verses that describes a cosmic phenomenon in which the sky is split apart and undergoes a change in color, expressed through the phrase Wardatan Kādihan. This verse has given rise to diverse interpretations, particularly between classical exegesis and contemporary scientific (tafsir ‘ilmi) interpretations. This article aims to analyze and compare the interpretation of Surah Ar-Rahman verse 37 in classical exegesis and contemporary scientific exegesis, while examining its relevance to the phenomenon of nebulae from the perspective of modern astronomy. This study employs a qualitative library research method using descriptive and comparative approaches. Primary data were obtained from classical Qur’anic commentaries, including Tafsir Ibn Kathir and Tafsir Al-Qurtubi. Contemporary scientific interpretations were drawn from Tafsir Al-Ayat Al-Kauniyyah, the Scientific Tafsir published by the Ministry of Religious Affairs of the Republic of Indonesia, and the works of contemporary Muslim scholars. The findings indicate that classical exegesis interprets Surah Ar-Rahman verse 37 as a description of cosmic events that will occur on the Day of Judgment, emphasizing linguistic analysis and transmitted narrations. In contrast, contemporary scientific exegesis relates the verse to astronomical phenomena, such as nebulae, through an interpretative approach that is indicative rather than definitive. This article concludes that the integration of Qur’anic exegesis and science should be carried out in a methodological and proportionate manner so as not to exceed the epistemological boundaries of Qur’anic interpretation.